IMPLEMENTASI DATA MINING UNTUK KARTU INDONESIA SEHAT BAGI MASYARAKAT KURANG MAMPU MENGGUNAKAN METODE CLUSTERING PADA DINAS SOSIAL KOTA PALEMBANG - Wulan Lestari; Fatoni Fatoni; Hutrianto Hutrianto (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
The Social Service Office of Palembang City is a government institution that is responsible for carrying out development in the field of social welfare, which covers all programs and activities that are intended to realize, foster and maintain, restore and develop social welfare carried out together as the responsibility of the government and society. In conducting data processing to determine the capable and underprivileged people as recipients of the Healthy Indonesia Card (KIS) with a process that takes a long time, given the large number of population data to be selected, especially in the city of Palembang. Then it can be raised into the research, namely